Penerapan Teori Belajar Behavioristik Skinner Dalam Pembelajaran Baca Tulis Al-Qur’an - murniyati murniyati; Suyadi Suyadi (Universitas Cokroaminoto Yogyakarta, 2021)
Behavioristic learning theory from B.F Skinner is the theory of learning which discusses the process of changing behavior. This behavior change is mentioned as a form of learning outcomes through a process of strengthening a new behavior which is also called operant conditioning. The purpose of this research is to find out how the application of Skinner's theory in Alam Nurul Islam IT Elementary School and the impact of the application of B.F Skinner’s behavioristic theory on learning to read and write Al-Qur'an. The writer uses descriptive qualitative method in conducting the research in order to explain the application of B.F Skinner's behavioristic theory. Through this research, the researchers tries to reveal the efforts of giving stimulus and repetition which is made by the teacher to the material being taught as well as the principles of Skinner which are applied in BTAQ learning. The result of this research shows that the application of B.F Skinner's behavioristic theory has resulted in a better change in student behavior in the form of increasing motivation, discipline, istiqomah behavior, and quality of memory.